2020
DOI: 10.3892/ol.2020.12153
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers predicting the chemotherapeutic outcomes of capecitabine and oxaliplatin in patients with gastric cancer

Abstract: The capecitabine and oxaliplatin (CapeOX) regimen is a commonly used adjuvant chemotherapeutic regimen for gastric cancer (GC). However, some patients exhibit a poor chemotherapy response due to genetic differences among individuals. Therefore, finding an effective sensitization strategy for CapeOX is important in the treatment of GC. The present study aimed to investigate the predictive biomarkers of the CapeOX chemotherapeutic outcomes for patients with GC. A total of 30 differentially expressed genes (DEGs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Previously, MATN3 was aberrantly methylated and expressed in gastric cancer and related to survival outcomes [28]. UPK1B expression was in relation to response to capecitabine and oxaliplatin and prognoses for gastric cancer patients [29]. GPX3 hypermethylation was in gastric cancer and correlated to lymph node metastases, tumor invasion depth, tumor differentiation as well as relapse [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, MATN3 was aberrantly methylated and expressed in gastric cancer and related to survival outcomes [28]. UPK1B expression was in relation to response to capecitabine and oxaliplatin and prognoses for gastric cancer patients [29]. GPX3 hypermethylation was in gastric cancer and correlated to lymph node metastases, tumor invasion depth, tumor differentiation as well as relapse [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is identified that UPK1B can be used as a biomarker to predict the chemotherapeutic outcomes of capecitabine and oxaliplatin in gastric cancer patients (89). The high expression of UPK1B in adjuvant capecitabine and oxaliplatin treated patients with GC was associated with poor outcomes.…”
Section: Tspan20/upk1bmentioning
confidence: 99%
“…It is overexpressed in GC and causes poor prognosis by affecting cell viability, invasion, and migration [19]. In recurrent GC, elevated UPK1B expression has a worse prognosis [20]. The mechanism for poor prognosis may be that UPK1B signi cantly affects the expression of critical genes in the Wnt/β-catenin signaling pathway in cancer cells [21].…”
Section: Discussionmentioning
confidence: 99%